Evaluation and Improvement of Business Processes in the Operational Division Using Business Process Improvement (BPI) (Case Study: PT. Mitrasukses Engineering Indonesia - Sinatriya, Ichi Rizqi; Hanggara, Buce Trias; Rachmadi, Aditya (Department of Informatics Engineering, 2024)
PT. Mitrasukses Engineering Indonesia (MEI) is a manufacturing company specializing in custom machine production. The company has an operational division responsible for managing product orders until they are delivered. The main problem in the operational division of PT. MEI is the inconsistency between product designs and customer needs, leading to machine design redesigns and delays in order processing. Therefore, a more detailed analysis of potential errors is required, followed by recommendations for improvement through business process improvement. The methodology used to analyze potential errors is the Failure Mode and Effect Analysis (FMEA) method. Meanwhile, the methodology used to provide improvement recommendations is the Business Process Improvement (BPI) method with the streamlining tools. The improvement measures adopted include streamlining tools such as Standardization, Upgrading, Simplification, Automation, and Error Proofing. Simulations will be conducted after modeling the improved business process based on the improvement recommendations. The simulations compare the time between the current business process model (as-is) and the improved business process model (to-be) to determine the percentage increase in efficiency. Efficiency occurs due to changes in process activities in the current business process that has been improved. The simulation results indicate an efficiency improvement in the product ordering process by 16.58%, material procurement process by 35.37%, production process by 38.85%, and product delivery process by 22.42%.